2020
DOI: 10.1037/bul0000225
|View full text |Cite
|
Sign up to set email alerts
|

Memory in autism spectrum disorder: A meta-analysis of experimental studies.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version.Permanent repository link: https://openaccess.city.ac.uk/id/eprint/23359/ Link to published version: http://dx. Abstract:To address inconsistencies in the literature on memory in Autism Spectrum Disorder (ASD), we report the first ever meta-analysis of short-term (STM) and episodic longterm (LTM) memory in ASD, evaluating the effects of type of material, type of retrieval and the role of inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 178 publications
4
76
0
8
Order By: Relevance
“…Together, the sequence of amplitude decrement on the P2 then FN400 potentials suggests a reduced integration of low-level perceptual into high-level conceptual information of pictures in ASD participants, associated with a reduced familiarity-based memory. This conclusion fits with recent EEG results of atypical integration between low-and high-level information with visual stimuli [Ortiz-Mantilla, Cantiani, Shafer, & Benasich, 2019;Wang, Yang, Liu, Shao, & Jackson, 2017], and recent model of visual episodic memory being less supported by semantic knowledge than verbal memory in individuals with ASD relative to TD controls [Desaunay et al, 2020;Semino et al, 2019].…”
Section: Reduced Early Processing Of Semantically Related Visual Infosupporting
confidence: 90%
“…Together, the sequence of amplitude decrement on the P2 then FN400 potentials suggests a reduced integration of low-level perceptual into high-level conceptual information of pictures in ASD participants, associated with a reduced familiarity-based memory. This conclusion fits with recent EEG results of atypical integration between low-and high-level information with visual stimuli [Ortiz-Mantilla, Cantiani, Shafer, & Benasich, 2019;Wang, Yang, Liu, Shao, & Jackson, 2017], and recent model of visual episodic memory being less supported by semantic knowledge than verbal memory in individuals with ASD relative to TD controls [Desaunay et al, 2020;Semino et al, 2019].…”
Section: Reduced Early Processing Of Semantically Related Visual Infosupporting
confidence: 90%
“…Given their link with each other, and their influence on cognitive capabilities, such as intelligence and academic achievement (13)(14)(15)(16)(17)(18), understanding the nuances and the extent of STM and WM impairments in ASD is a crucial first step in improving cognitive outcomes in this population. The current literature points to a more severe deficit in ASD in visual, especially visuospatial, aspects of STM and WM, rather than in verbal STM and WM (10,(19)(20)(21)(22)(23), though people with ASD exhibit impairments in both modalities (11,24). Neuroimaging work has additionally shown that individuals with ASD exhibit atypical neural activity and connectivity during visual STM tasks (25)(26)(27) and in both visual and verbal WM tasks (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 97%
“…Adults with autism spectrum disorder (ASD) demonstrate difficulties with a variety of executive functions (1)(2)(3)(4), one of which is working memory (WM), which refers to the ability to hold and manipulate information in mind (5,6). WM is related to short-term memory (STM), which involves the mental storage of information for a short period of time (7,8), and which is also impaired in adults with ASD (9)(10)(11)(12). Given their link with each other, and their influence on cognitive capabilities, such as intelligence and academic achievement (13)(14)(15)(16)(17)(18), understanding the nuances and the extent of STM and WM impairments in ASD is a crucial first step in improving cognitive outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%
“…In explicit memory, this might be demonstrated by our ability to remember the order of digits of someone's phone number, while in implicit memory this might be indicated by our increasing proficiency at carrying out sequences of behaviors that we repeatedly execute without consciously trying to remember them (e.g., typing). Serial order learning is thus expressed in multiple memory systems [see Hurlstone, Hitch, & Baddeley, 2014; Page & Norris, 2009], and in the context of autism it is now well established that explicit serial order memory is a source of difficulty, while implicit serial order learning is preserved [see Desaunay et al, 2020; Foti, De Crescenzo, Vivanti, Menghini, & Vicari, 2015, for reviews]. Although early studies by Hermelin and O'Connor had indicated relatively preserved memory for the serial order of short lists of words or pictures [Hermelin & O'Connor, 1970], over a dozen studies since then have shown that autistic children and adults demonstrate difficulties on digit‐span and visuospatial span tasks, with group differences characterized by a medium effect size [Desaunay et al, 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Serial order learning is thus expressed in multiple memory systems [see Hurlstone, Hitch, & Baddeley, 2014; Page & Norris, 2009], and in the context of autism it is now well established that explicit serial order memory is a source of difficulty, while implicit serial order learning is preserved [see Desaunay et al, 2020; Foti, De Crescenzo, Vivanti, Menghini, & Vicari, 2015, for reviews]. Although early studies by Hermelin and O'Connor had indicated relatively preserved memory for the serial order of short lists of words or pictures [Hermelin & O'Connor, 1970], over a dozen studies since then have shown that autistic children and adults demonstrate difficulties on digit‐span and visuospatial span tasks, with group differences characterized by a medium effect size [Desaunay et al, 2020]. By contrast, implicit serial order learning, which is typically assessed using Serial Reaction Time Tasks [SRT; Nissen & Bullemer, 1987], is generally preserved.…”
Section: Introductionmentioning
confidence: 99%